Lectin affinity chromatography and electrophoretic properties of human platelet gamma-glutamyl transferase - (:unkn) unknown (CARFAX PUBLISHING, 2000)
The sialoglycoprotein, gamma-glutamyl transferase (GGT, gamma-GT, EC 2.3.2.2) is a membrane enzyme found in many cells including platelets and leukocytes. In platelets GGT converts leukotriene C-4 (LTC4) to leukotriene D-4 (LTD4) and is involved in glutathione metabolism. In this study, human platelet GGT was solubilized with Triton X-100 and purified by lectin affinity chromatography on Con A Sepharose 4B to determine its electrophoretic properties. The specific activity of purified GGT was 236 mU/mg protein; 73.7% of human platelet GGT activity was found bound to Con A and 50% of the bound activity was released with 0.3 mol/l methyl alpha-D-mannopyranoside. We observed that human platelet GGT has only one isoenzyme band showing a carbohydrate stained band near the origin on polyacrylamide gel electrophoresis (PAGE). The electrophoretic mobility of papain-solubilized GGT was higher than that of Triton X-100-solubilized GGT at PAGE. Also GGT activities were determined on neuraminidase, trypsin or n-butanol-DIPE (diisopropyl ether)-treated Triton X-100-solubilized membrane fractions. This characterization may be useful when trying to establish the contribution of platelet GGT to serum GGT activity. This marker may reflect the extent of platelet activation.
Keywords: HUMAN-LIVER; TRANSPEPTIDASE; GLUTAMYLTRANSFERASE; KIDNEY; BLOOD; GENES; BRAIN; RAT; METABOLISM; MEMBRANE